(untitled) - Astor, Gerald (Hoboken, N.J., 2006)
The Korean War, the Bay of Pigs, the Cuban Missile Crisis, Vietnam, Cambodia, Lebanon, El Salvador, Grenada, Iran-Contra, Nicaragua, Panama, the Gulf War, Somalia, Kosovo, Afghanistan, Iraq
Keywords: Presidents,Presidents,Tổng thống,Tổng thống; History,History,Lịch sử,Lịch sử; 20th century,21st century,Thế kỷ 20,Thế kỷ 21; United States,United States,Hoa Kỳ,Hoa Kỳ